(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
Speaking skill is considered the most important skill, as it allows people to freely express their emotions and thoughts. Through speaking, they can communicate with foreigners. Communication is an opportunity to open the doors to the world. Whether in business or education, it is essential in all fields. Speaking is a fundamental skill in communication, and improving it requires a strategic combination of cognitive, linguistic, and social approaches. This paper explores the science behind language acquisition, the role of psychological factors, and practical methods for enhancing speaking abilities. We review existing research and provide evidence-based strategies for learners and educators.